(untitled) (Revista de Investigaciones Universidad del Quindío, 2016)
On this project, we have considered the anthropometrics of the human arm, taking in consideration the movements and angles of the elbow and wrist by developing a prototype for the first and second phases of rehabilitation as the main goal the patient could achieve full joints mobility. The implementation of this prototype consists in four different adaptations, one for each movement, an interface electronic board of sensors, a control board, and a graphical interface of the user where the physiotherapist is able to set up a personalized rehabilitation cycle responding to the patient needs. We have done field tests of the prototype with a patient with elbow and wrist fracture diagnosis. The results of these tests showed an improvement in the mobility of both joints through a small number of rehabilitation sessions. Thus, it is concluded that the prototype allows the patient the progressive reach of angles nearer to the angular limits of pronation-supination of the elbow and flexion-extension of the wrist, with a reduction of 50% of number of session using conventional methods.